2013
DOI: 10.1080/00207543.2013.801570
|View full text |Cite
|
Sign up to set email alerts
|

Towards a formal manufacturing reference ontology

Abstract: 1 In a seminal work published in 1952, "The chemical basis of morphogenesis"-considered as the true start point of the modern theoretical biology-, A. M. Turing established the core of what today we call "natural computation" in biological systems, intended as self-organizing dynamic systems. In this contribution we show that the "intentionality", i.e., the "relation-to-object" characterizing biological morphogenesis and cognitive intelligence, as far as it is formalized in the appropriate ontological interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Ontology is the formalized description of concepts/relationships and is often designed to be expressed through standardized formal languages (like OWL and RDFS). Researchers over the years have contributed to the development of ontology in the manufacturing domain and a list of relevant ontology has been reviewed and summarized by Zahid Usman et al [14]. However, the ontology for providing a common and consistent understanding for the key performance assurance activity in the manufacturing domains, has been rarely studied.…”
Section: Ontological Formulation Of Pa Informationmentioning
confidence: 99%
“…Ontology is the formalized description of concepts/relationships and is often designed to be expressed through standardized formal languages (like OWL and RDFS). Researchers over the years have contributed to the development of ontology in the manufacturing domain and a list of relevant ontology has been reviewed and summarized by Zahid Usman et al [14]. However, the ontology for providing a common and consistent understanding for the key performance assurance activity in the manufacturing domains, has been rarely studied.…”
Section: Ontological Formulation Of Pa Informationmentioning
confidence: 99%
“…As part of this it developed a set of core concepts to specifically enable the sharing of knowledge across design and production domains. Design and production concepts were specialised from generic foundation *Response to Reviewers -no author names/affiliations ontology concepts in order to provide the required level of interoperability [5].…”
Section: Introductionmentioning
confidence: 99%
“…From this a set of core concepts were developed representing the design and manufacturing domains. It was shown that it was possible to specialise these core concepts to enable interoperability (Usman et al, 2013).…”
Section: Manufacturing Reference Ontologiesmentioning
confidence: 99%